IMPLEMENTASI PEMBELAJARAN MULTIMODEL BERBASIS PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PENCAPAIAN KOMPETENSI DASAR FISIKA DI SLTP - Tiur Maria, Haratua (Universitas Tanjungpura, 2010)
The aim of this research is to increase the concepts understanding and the student's competences to measure through the application of contextual teaching and learning models. The subject of this research was abut 40 the first level student's of SLTPN 1 Pontianak. The typed of this research was Classrom Action Research (CAR) by two cycles. The aim of the cycle was Contextual Teaching and Learning that focused about base units and derived' units. Through this research, it will found the information about comprehension profile and student's competences related to the measurement. The achievement of the claasroom action research's cycles was the mastery learning of 70% student that can be done the test minimal 65%. In collecting data the measurement test is done writtenly and performance test. The instruments that used in this research are the concepts understanding and performance test, observation guidance and also the field notes. From the research result, it shown that the qualities of students' concept understanding and competences about measurement are increases. The students' concepts understanding can increase from the average 49,25% to 78,75%, and the students' competence about measurement increase too from the average 42,19% to 77,81%. The result study that analyzed by Mc'Nemar test is showing the differences significantly between the result of pretest and posttest to conceptual understanding. Therefore, in general, the application of contextual teaching and learning multimodel can increase the the students' result study significantly.Key word : Multimodel Teaching, Competences, The Contextual Aproach.